Facile synthesis of nanoparticle-stacked tungsten-doped nickel iron layered double hydroxide nanosheets for boosting oxygen evolution reaction. Issue 16 (17th April 2020) - Wu, Libo; Yu, Luo; Zhang, Fanghao; Wang, Dezhi; Luo, Dan; Song, Shaowei; Yuan, Chuqing; Karim, Alamgir; Chen, Shuo; Ren, Zhifeng
Abstract : Nanoparticle-stacked tungsten-doped nickel iron layered double hydroxide (Ni–Fe–W LDH) nanosheets have been synthesized through a facile water bath reaction as efficient water oxidation catalyst. Abstract : Developing highly efficient and cost-effective water oxidation catalysts to enhance the oxygen evolution reaction (OER) remains a significant challenge for electrochemical water splitting. Here, ultrathin tungsten-doped nickel iron layered double hydroxide (Ni–Fe–W LDH) nanosheets, which are composed of nanoparticles with size of 2 to 6 nanometers, have been directly grown on nickel foam (NF) using a facile and scalable water bath reaction. When applied as a catalyst for OER catalysis, this self-supported Ni–Fe–W LDH/NF shows superb OER activity, requiring low overpotentials of only 247 and 320 mV to attain current densities of 100 and 1000 mA cm −2, respectively, with a small Tafel slope of 55 mV dec −1 in 1.0 M KOH electrolyte. The high catalytic activity is attributed to the unique open porous structure, high density of crystalline–amorphous phase boundaries, abundant active sites, and enhanced conductivity resulting from the combination of W doping and Ni–Fe LDH. This work presents a general approach toward the large-scale fabrication of inexpensive trimetallic LDH-based OER electrocatalysts.